Antibiotic Resistance Patterns in Faecal E. coli: A Longitudinal Cohort-Control Study of Hospitalized Horses - Ahmed, Mohamed O.; Williams, Nicola J.; Clegg, Peter D.; Baptiste, Keith E.; Bennett, Malcolm (IntechOpen, 2012)
None